Business Intelligence–Based Digital Marketing Strategy for SME Market Expansion - Supriyadi, Supriyadi; Pranyoto, Edi (Universitas Dharma Wacana, 2025)
Small and medium-sized enterprises (SMEs) face increasing challenges in expanding their markets due to limited resources, intense competition, and rapidly changing digital consumer behavior. This study proposes a Business Intelligence (BI)–based digital marketing strategy as a data-driven approach to support SME market expansion by integrating data from multiple digital channels, including social media, e-commerce platforms, CRM systems, and website analytics, to generate actionable insights for strategic decision-making. Using a mixed-method approach that combines quantitative analysis of digital marketing performance with qualitative managerial perspectives, the study applies key BI components—such as data warehousing, dashboards, predictive analytics, and customer segmentation—to enhance targeting, personalization, campaign effectiveness, and resource allocation. The findings indicate that SMEs adopting BI-supported digital marketing achieve significantly higher customer acquisition, engagement, and conversion rates than those relying on traditional approaches, while predictive analytics enables more accurate demand forecasting and identification of high-potential market segments. The study also identifies critical success factors, including data integration capability, analytical skill development, and strategic alignment between business objectives and marketing activities. Despite constraints related to technical expertise and budget, scalable BI tools and cloud-based platforms make advanced analytics increasingly accessible. Overall, the research contributes a practical framework demonstrating that Business Intelligence is a key enabler of marketing efficiency, evidence-based decision-making, and sustainable market expansion for SMEs in the digital economy.